E-062 Stent-assisted embolization of 71 anterior cerebral artery aneurysms. (4th July 2012) - Johnson, A; Munich, S; Heiferman, D; Lopes, D
Abstract : Introduction: Anterior cerebral artery aneurysms (ACAAs) comprised over half of the ruptured aneurysms in the International Subarachnoid Trial. These lesions tend to rupture at a smaller size than those at other locations. Endovascular treatment of ACAAs has provided excellent results, but until the introduction of intracranial stents, many ACAAs could not be treated without craniotomy. The current study analyzes the results of ACAA treatment using stent-assisted embolization. Materials and Methods: After being offered the options of observation, endovascular repair, and microsurgical treatment, 69 patients with 71 ACAAs underwent stent-assisted aneurysm repair. Three aneurysms were distal ACAAs. Eight were 10 mm or more in greatest diameter, and all aneurysms were <15 mm. Follow-up angiography was performed 6 months after treatment; then patients were followed with annual magnetic resonance angiography. Immediate, mid-term, and long-term radiographic results and complications were analyzed. Results: After stent-assisted embolization, 33 (46.5%) ACAAs were completely occluded, 18 had residual neck, and 20 had residual filling. At first radiographic follow-up, 39 of 58 (67.2%) showed complete occlusion. Four aneurysms required retreatment, one with another stenting procedure. After stable initial follow-up angiography, no aneurysms worsened clinically or radiographically during the follow-up period. One patient treated with a three-stent construct died of periprocedural hemorrhage. One major stroke occurred during a hip surgery while the patient discontinued anti-platelet medications. These cases were the only aneurysm-related major morbidity (1.4%) and mortality (1.4%) during the follow-up period. Conclusion: Stent-assisted aneurysm treatment was a safe and effective option in this series of ACAAs with complex anatomy. Contrary to prevailing opinions regarding the durability of microsurgical and endovascular repair, aneurysms in the anterior cerebral artery distribution may be more likely to recur after clipping, and stent-assisted embolization may be durable after stable initial follow-up. Competing interests: A Johnson: None. S Munich: None. D Heiferman: None. D Lopes: Stryker, ev3, Penumbra.